Scanning electron microscopy of coffee beans subjected to different forms of processing and drying - Borém, Flávio Meira; Oliveira, Pedro Damasceno; Isquierdo, Eder Pedroza; Giomo, Gerson da Silva; Saath, Reni; Cardoso, Renan Alves (Coffee Science - ISSN 1984-3909, 2013)
The objective of the present work was to evaluate changes in the structure of coffee beans processed and dried in different ways. The experiment was conducted with two types of processing: dry and wet, and four drying methods: drying on ground and mechanical drying with air heated to 50/40 ° C, 60/40 ° C and 40/60 ° C, where the temperature was changed when the coffee beans reached 30% ± 2% (db), with supplementation of dehydrated to 11% ± 1% (wb). The mechanical drying system used consisted of three fixed bed dryers, which allows control of temperature and flow rate of drying. During the experiment, data were collected to assess the dynamics of drying.After treatment application, the coffee beans were subjected to studies in a scanning electron microscope (SEM). The observation of the coffee beans by SEM showed that the drying temperature of 50/40 ° C pulped coffees showed similar results to those dried in cafes, with a small contraction of the cells, without signs of rupture. It was observed that utilization of the drying temperature 40/60 ° C was the most damage caused to the structures of cells, regardless of the type of processing. It was found that the coffee prepared by dry showed higher destruction of the cellular components of the coffee pulped and, a longer exposure of coffee to the drying process.